Extended screen time and dry eye in youth. Issue 5 (October 2022) - Muntz, Alex; Turnbull, Philip RK; Kim, Andy D; Gokul, Akilesh; Wong, Daniel; Tsay, Tricia Shau-Wei; Zhao, Karyn; Zhang, Simo; Kingsnorth, Alec; Wolffsohn, James S; Craig, Jennifer P
Abstract: Purpose: Extended screen time amongst youth is a pervasive global phenomenon, with wide-ranging implications for health and quality of life. Dry eye disease is increasingly reported as emerging in paediatric populations and is associated with modified blinking behaviour during extended screen time. This study sought to evaluate spontaneous blink rates, dry eye symptomology and screen use habits of young extended screen time users. Methods: Attendees of a gaming convention in Auckland, NZ, completed a self-directed iPad-based survey on personal screen use habits and ocular symptoms using the 5-item Dry Eye Questionnaire (DEQ-5) and the Symptom Assessment in Dry Eye (SANDE) questionnaire. Blink rate was covertly and concomitantly recorded using the front-facing iPad camera and quantified by automated software. A validated, self-assessment blink test was administered as a proxy for tear film stability measurements. Results: A total of 456 respondents (mean age ± SD: 24 ± 10 years, range: 13 – 75, 38% female) reported an average weekly screen time of 43.7 ± 24.4 h. DEQ-5 and SANDE scores were 10 ± 3 and 34 ± 19; 90% of respondents qualified as symptomatic for dry eye disease (DEQ-5 ≥ 6). Blink test results suggested a tear film stability < 10 s in 24% of cases. Poorer symptomology correlated with increased screen use, elevated blink rates and reduced proxy tear film stability (r = 0.15 to 0.22, all p < 0.01). Conclusion: Extended screen time in a young population was associated with blinking behaviour and symptomology consistent with patients with dry eye. Implementing routine clinical screening, educational interventions, and developing official guidance on safe screen use may help prevent an accelerated degradation of ocular surface health and quality of life in young people.